2015 update of the evidence base: World Allergy Organization anaphylaxis guidelines. Issue 1 (December 2015) - Simons, F.; Ebisawa, Motohiro; Sanchez-Borges, Mario; Thong, Bernard; Worm, Margitta; Tanno, Luciana; Lockey, Richard; El-Gamal, Yehia; Brown, Simon; Park, Hae-Sim; Sheikh, Aziz
Abstract The World Allergy Organization (WAO) Guidelines for the assessment and management of anaphylaxis provide a unique global perspective on this increasingly common, potentially life-threatening disease. Recommendations made in the original WAO Anaphylaxis Guidelines remain clinically valid and relevant, and are a widely accessed and frequently cited resource. In this 2015 update of the evidence supporting recommendations in the Guidelines, new information based on anaphylaxis publications from January 2014 through mid- 2015 is summarized. Advances in epidemiology, diagnosis, and management in healthcare and community settings are highlighted. Additionally, new information about patient factors that increase the risk of severe and/or fatal anaphylaxis and patient co-factors that amplify anaphylactic episodes is presented and new information about anaphylaxis triggers and confirmation of triggers to facilitate specific trigger avoidance and immunomodulation is reviewed. The update includes tables summarizing important advances in anaphylaxis research.